The Effect of Business Strategies and Financial Reporting Irregularities On Audit - Rahman, Annisaa; Zakary, Judith; Rahayu, Rita (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2023)
This research aims to examine and analyze the effect of business strategy and financial reporting irregularities on audit fees. Business strategy is measured by six comprehensive sizes: research and development ratios, employee ratios, revenue changes, sales load ratios, employee turnover ratios, and capital intensity. Financial reporting irregularities are measured by the indication of deviation of financial statements, and the audit fee is measured by the company's logarithmic number of audit fees. Sample selection using purposive sampling method and selected 314 companies that meet the criteria for this study. The research was conducted from 2017-to 2019. The results of this study indicate that financial reporting irregularities and business strategy have a significant effect on audit fees. In summary, the results of this study support the view that the company's financial information and the complexity of the business represented in the company's business strategy are essential considerations for auditors in setting audit fees. The research findings prove that a business strategy that represents the complexity of the company's business and indications of financial statement irregularities will affect the cost of external auditors. In general, this research has implications that management policies and actions will have an impact not only on operational costs, but also on agency costs. Minimizing irregularities financial statements will reduce the costs borne by the company. Therefore, shareholders must monitor the policies and actions taken by the company. Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh strategi bisnis dan penyimpangan pelaporan keuangan terhadap fee audit. Strategi bisnis diukur dengan enam ukuran komprehensif: rasio penelitian dan pengembangan, rasio karyawan, perubahan pendapatan, rasio beban penjualan, rasio perputaran karyawan, dan intensitas modal. Penyimpangan pelaporan keuangan diukur dengan indikasi penyimpangan laporan keuangan, dan fee audit diukur dengan jumlah logaritma fee audit perusahaan. Pemilihan sampel menggunakan metode purposive sampling dan terpilih 314 perusahaan yang memenuhi kriteria penelitian ini. Penelitian ini dilakukan dari tahun 2017 hingga 2019. Hasil dari penelitian ini menunjukkan bahwa penyimpangan pelaporan keuangan dan strategi bisnis berpengaruh signifikan terhadap fee audit. Secara ringkas, hasil penelitian ini mendukung pandangan bahwa informasi keuangan perusahaan dan kompleksitas bisnis yang direpresentasikan dalam strategi bisnis perusahaan merupakan pertimbangan penting bagi auditor dalam menetapkan fee audit. Temuan penelitian membuktikan bahwa strategi bisnis yang merepresentasikan kompleksitas bisnis perusahaan dan indikasi penyimpangan laporan keuangan akan mempengaruhi biaya auditor eksternal. Perusahaan sebaiknya meminimalisir kesalahan atau penyimpangan dalam laporan keuangan, agar tidak berdampak pada peningkatan fee audit. Secara umum, penelitian ini berimplikasi bahwa kebijakan dan tindakan manajemen akan berdampak tidak hanya pada biaya operasional, tetapi juga pada biaya keagenan. Meminimalkan penyimpangan laporan keuangan akan mengurangi biaya yang ditanggung perusahaan. Oleh karena itu, pemegang saham harus memantau kebijakan dan tindakan yang diambil oleh perusahaan.